C14 A stress level test as part of an assessment battery for phenotyping minipigs transgenic for huntington's disease. (13th September 2016) - Schuldenzucker, Verena; Schubert, Robin; Freisfeld, Frauke; Rieke, Lorena; Matheis, Tamara; Motlik, Jan; Schramke, Sarah; Reilmann, Ralf
Abstract : Background: Transgenic (tg) minipigs (124 Q) serve as large animal model for pre-clinical studies in HD. Several studies showed a higher cortisol level in HD patients in comparison to control groups. We therefore developed a "Stress Level Test" assessing cortisol and other autonomic measures as possible surrogate markers of a behavioural challenge in an assessment battery for minipigs. Objective: Test the feasibility and tolerability of the "Stress Level Test" in tgHD Libechov minipigs and explore possible differences compared to wildtype (wt) minipigs. Methods: 32 female Libechov minipigs, 18 wt and 14 tgHD, were housed in six mixed groups (wt and tg) at the animal facility of the University of Muenster, Germany, under controlled enrichment conditions. Cortisol samples were collected at standardised times before, during and after hoof trimming. Exposure to trimming in a custom-made hoof-trimming stand induced stress in the animals. A pulse oximeter was attached to the animal's tail and heart, respiratory rate and body temperature were measured as surrogates of stress level. Results: The test was feasible and safe and animals showed a good tolerance of the method. Cortisol levels and physiological data was collected reliably and repetitively. Cross sectional and longitudinal data analysis is now in progress. Conclusion: Implementation of the "Stress Level Test" in studies with tgHD minipigs is feasible and well tolerated. Studies are ongoing to assess whether the behaviour and surrogate markers differ between tgHD and wt minipigs. Acknowledgement: Funded by the CHDI Foundation.